Analisis Jaringan Komunikasi Koalisi Partai Pemilihan Umum Presiden 2014 dan 2019 - Abraham Wahyu Nugroho; Andreas Pandiangan (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2019)
Indonesia is a democracy country with multiparty system. This situation encourages the emergence of party coalitions to be able to compete in political contestation, especially in general elections. This research aims to describe the structure of political party coalitions and the process of forming a coalition by political elites in presidential elections in 2014 and 2019. This research uses data sources from the news clippings of Gatra Magazine, edition March 24 - June 11, 2014 and July 25 - September 5, 2018. The data was analyzed by communication network analysis (CNA) method by using UCINET software. Based on CAN method, the coalition of political parties in the presidential election in 2014 and 2019 is not solid and tend to conflicts, because the political elites prioritize more on the number of relationships than cohesiveness of coalition networks. The other finding is Jokowi becomes popular political actor who has important role to form political party networks in presidential elections in 2014. Susilo Bambang Yudhoyono still has important role in forming political party networks in presidential elections in 2019.